Breathing through a troubled life – a phenomenological-hermeneutic study of chronic obstructive pulmonary disease patients’ lived experiences during the course of pulmonary rehabilitation - Charlotte Simonÿ; Ingrid Charlotte Andersen; Uffe Bodtger; Regner Birkelund (International Journal of Qualitative Studies on Health & Well-Being, 2019)
Purpose: Exploring real-life experiences of Chronic Obstructive Pulmonary Disease (COPD) patients during rehabilitation can contribute with new knowledge of what has significance for their participation and chance for improved health and well-being. Therefore, this study aims to gain in-depth knowledge of COPD patients’ lived experiences while following standard pulmonary out-patient rehabilitation. Methods: Combined participant observations and interviews were conducted among 21 participants in pulmonary rehabilitation. A three-leveled phenomenological-hermeneutic interpretation was applied. Results: Living with COPD was challenging due to dyspnea and other physical troubles. This caused a lack of trust in the body and complicated rehabilitation participation. When improving management of breath during rehabilitation, the patients gained a new sense of trust in the body. This was accompanied by a nascent hope and increased well-being. However, not succeeding in this left patients with a persistent lack of hope. Conclusions: Comprehensive troubles in living with COPD paradoxically prevents patients’ prospect of overcoming a perceived lack of trust in their body during standard pulmonary rehabilitation. Enhancing breath management has a significant impact on COPD patients’ trust in own capabilities to improve well-being and health. Future rehabilitation must accommodate COPD patients’ troubles by longer-lasting, well-coordinated, individually supportive and more easily accessible programmes.